Penerapan Kombinasi Ankle Pump Exersice dan Elevasi Kaki 30̊ terhadap Derajat Edema Pasien HD di Kota Palembang - Ketut Lidia Wati; Aniska Indah Fari; Bangun Dwi Hardika (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Edema is an excessive accumulation of fluid between the cells of body tissues. In patients with chronic kidney disease undergoing hemodialysis, the kidneys are unable to excrete metabolic waste products and toxins, which leads to edema. One non-pharmacological intervention that can be provided is a combination therapy of Ankle Pump Exercise and 30° leg elevation to reduce the degree of edema.This final nursing scientific paper used a case study design. The intervention was carried out on June 5th, June 9th, and June 12th, 2026, at the Hemodialysis Room of Bhayangkara Mohamad Hasan Hospital Palembang. After the Ankle Pump Exercise and 30° leg elevation therapy, the results of edema assessment were: Mr. Z had grade II edema with a depth of 3 mm and a duration of 10 seconds, Mr. G had grade I edema with a depth of 2 mm and a duration of 3 seconds, and Mr. D had grade II edema with a depth of 3 mm and a duration of 10 seconds. The application of EBP through Ankle Pump Exercise and 30° leg elevation therapy was effective in reducing the degree of edema in hemodialysis patients.